2018
DOI: 10.3324/haematol.2017.168401
|View full text |Cite
|
Sign up to set email alerts
|

A phase II multicenter study of the anti-CD19 antibody drug conjugate coltuximab ravtansine (SAR3419) in patients with relapsed or refractory diffuse large B-cell lymphoma previously treated with rituximab-based immunotherapy

Abstract: This phase II, single-arm, multicenter study examined the efficacy and safety of coltuximab ravtansine (an anti-CD19 antibody drug conjugate) in 61 patients with histologically documented (de novo or transformed) relapsed or refractory diffuse large B-cell lymphoma who had previously received rituximab-containing immuno-chemotherapy. Patients had received a median of 2.0 (range 0-9) prior treatment regimens for diffuse large B-cell lymphoma and almost half (45.9%) had bulky disease (≥1 lesion >5 cm) at trial e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(28 citation statements)
references
References 38 publications
0
28
0
Order By: Relevance
“…The clinical efficacy and safety of SAR3419 monotherapy were evaluated in a phase II multicenter study. Eighteen of 41 patients with r/r DLBCL at dose 55 mg/m 2 obtained ORR (43.9%), with a median DoR of 4.7 months [ 71 ]. Another CD19-targeted ADC ADCT-402 (loncastuximab tesirine) comprising pyrrolobenzodiazepine dimer toxin showed early promise for patients DLBCL.…”
Section: Monoclonal Antibodies and Antibody–drug Conjugatesmentioning
confidence: 99%
“…The clinical efficacy and safety of SAR3419 monotherapy were evaluated in a phase II multicenter study. Eighteen of 41 patients with r/r DLBCL at dose 55 mg/m 2 obtained ORR (43.9%), with a median DoR of 4.7 months [ 71 ]. Another CD19-targeted ADC ADCT-402 (loncastuximab tesirine) comprising pyrrolobenzodiazepine dimer toxin showed early promise for patients DLBCL.…”
Section: Monoclonal Antibodies and Antibody–drug Conjugatesmentioning
confidence: 99%
“…Immunotherapy has become one of the most promising treatments for refractory/relapsed B cell lymphoma [1, 2]. Among immunotherapies, chimeric antigen receptor T (CAR T) cell immunotherapy has recently been found to be a highly effective treatment for common pre-B cell acute lymphoblastic leukemia and for relapsed or refractory diffuse large B-cell lymphoma (DLBCL), resulting in approximately a 40% durable response [3–6].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the inherent biological function of CD79b as a component of B-cell receptor (BCR) complex enables the efficient internalization and delivery of the bound ADC to the lysosomes, resulting in highly potent cancer cell killing [83,84]. On the other hand, while CD19 is a prototypical target of B-cell cancers for T cell engaging bsAbs (see above) or CAR-T cells [85] and coltuximab ravtansine (SAR3419, an anti-CD19 ADC) has also been evaluated in clinical trials (NCT01472887) [86], the antigen was found to internalize only in CD21-negative cells [87], exemplifying a technical hurdle of antigen internalization associated with the target selection for ADC.…”
Section: Target Antigensmentioning
confidence: 99%